T cell-based targeted immunotherapies for patients with multiple myeloma - Wang, Lei; Jin, Nan; Schmitt, Anita; Malcherek, Georg; Hundemer, Michael; Mani, Jiju; Hose, Dirk; Raab, Marc-Steffen; Ho, Anthony Dick; Goldschmidt, Hartmut; Schmitt, Michael (International journal of cancer, 2015)
Despite high-dose chemotherapy followed by autologs stem-cell transplantation as well as novel therapeutic agents, multiple myeloma (MM) remains incurable. Following the general trend towards personalized therapy, targeted immunotherapy as a new approach in the therapy of MM has emerged. Better progression-free survival and overall survival after tandem autologs/allogeneic stem cell transplantation suggest a graft versus myeloma effect strongly supporting the usefulness of immunological therapies for MM patients. How to induce a powerful antimyeloma effect is the key issue in this field. Pivotal is the definition of appropriate tumor antigen targets and effective methods for expansion of T cells with clinical activity. Besides a comprehensive list of tumor antigens for T cell-based approaches, eight promising antigens, CS1, Dickkopf-1, HM1.24, Human telomerase reverse transcriptase, MAGE-A3, New York Esophageal-1, Receptor of hyaluronic acid mediated motility and Wilms' tumor gene 1, are described in detail to provide a background for potential clinical use. Results from both closed and on-going clinical trials are summarized in this review. On the basis of the preclinical and clinical data, we elaborate on three encouraging therapeutic options, vaccine-enhanced donor lymphocyte infusion, chimeric antigen receptors-transfected T cells as well as vaccines with multiple antigen peptides, to pave the way towards clinically significant immune responses against MM.